Serum levels of melatonin may contribute to the pathogenesis of heart failure in children with median age of 1 year - Yao Wu; Feifei Si; Li Luo; Qijian Yi (Elsevier, 2018)
Objective: Melatonin has a protective role in adults with cardiovascular disease, but the effects of melatonin in children with cardiac dysfunction are not well understood. This study was designed to explore the variations in melatonin, myeloperoxidase, and caspase-3 levels in children suffering from heart failure. Methods: Seventy-two pediatric patients with heart failure and twelve healthy children were enrolled in this study. A modified Ross scoring system was used to evaluate clinical cardiac function. Patients with a score of >2 points were included in the study and were divided into three groups according to severity of heart failure: mild (score: 3-6), moderate (score: 7-9), and severe (score: 10-12). Echocardiographic parameters, laboratory data, and serum levels of melatonin, myeloperoxidase, and caspase-3 were measured and analyzed in all patients. Results: Compared with patients with mild and moderate heart failure, patients in the severe heart failure group had significantly decreased left ventricular ejection fraction (p < 0.001), and significantly increased serum melatonin levels (p = 0.013) and myeloperoxidase levels (p < 0.001). Serum melatonin levels were positively correlated with serum caspase-3 levels (p < 0.001). The optimal cutoff values of serum melatonin levels for the diagnosis of severe heart failure and primary cardiomyopathy in pediatric patients with heart failure were 54.14 pg/mL and 32.88 pg/mL, respectively. Conclusions: Serum melatonin and myeloperoxidase levels were increased in children with severe heart failure. It is likely that increasing melatonin levels may act as a compensatory mechanism in pediatric children with heart failure. Resumo: Objetivo: A melatonina possui um papel protetor em adultos com doença cardiovascular, porém os efeitos da melatonina em crianças com disfunção cardíaca não são bem entendidos. O estudo foi projetado para explorar a variação nos níveis de melatonina, mieloperoxidase e caspase 3 em crianças que sofrem de insuficiência cardíaca. Métodos: 72 pacientes pediátricos com insuficiência cardíaca e 12 crianças saudáveis foram inscritos no estudo. Um sistema de classificação de Ross modificada foi utilizado para avaliar a função cardíaca clínica. Os pacientes com escore de > 2 pontos foram incluídas no estudo e foram divididos em três grupos de acordo com a gravidade da insuficiência cardíaca: leve (escore: 3-6), moderada (escore: 7-9) e grave (escore: 10-12). Os parâmetros ecocardiográficos, dados laboratoriais e níveis séricos de melatonina, mieloperoxidase e caspase 3 foram medidos e analisados em todos os pacientes. Resultados: Em comparação aos pacientes com insuficiência cardíaca de gravidade leve e moderada, os pacientes no grupo de insuficiência cardíaca grave apresentaram redução significativa da fração de ejeção do ventrículo esquerdo (p < 0,001) e aumento significativo nos níveis séricos de melatonina (p = 0,013) e níveis de mieloperoxidase (p < 0,001). Os níveis séricos de melatonina foram positivamente correlacionados com os níveis séricos de caspase 3 (p < 0,001). Os valores de corte ideais dos níveis séricos de melatonina para diagnóstico de IC e cardiomiopatia primária em pacientes pediátricos com insuficiência cardíaca foram 54,14 pg/mL e 32,88 pg/mL, respectivamente. Conclusões: Os níveis séricos de melatonina e mieloperoxidase mostraram aumento em crianças com insuficiência cardíaca grave. Especulamos se o aumento nos níveis de melatonina pode agir como um mecanismo compensatório em crianças pediátricas com insuficiência cardíaca. Keywords: Melatonin, Myeloperoxidase, Capsase-3, Heart failure, Pediatric patients, Palavras-chave: Melatonina, Mieloperoxidase, Caspase 3, Insuficiência cardíaca, Pacientes pediátricos